Evaluation of the use of sulfadoxine-pyrimethamine (SP) intermittent treatment (IPT) to prevent malaria during pregnancy in Ndola, Zambia. - Mulamba, M. (Stellenbosch : Stellenbosch University, 2016)
Thesis (MFamMed)--Stellenbosch University, 2009.